Liderazgo, la competencia esencial que transformó una empresa colombiana en un gigante internacional: el caso de Cementos Argos (2011)
Cementos Argos has long been regarded as a giant in the Colombian cement manufacturing industry. Thanks to its large capacity to reach a solid position in the domestic market as well as to its unconventional internationalization strategies, it has earned a prominent place in Colombia and other Latin American countries and even in such strong markets as the United States. This research study is an effort to document the international experience of Argos from the perspective of the most widely accepted theories of internationalization available in specialized literature, using the methodological case-study approach. As a result, it was found that retention strategies and the organizational redesign generated by the leadership of corporative management, are vital tools to ensure growth of the company in local and external markets.